Changes in height-for-age of Egyptian children from 1995 to 2014: Implications for improving child health outcomes - Hashad, Reem; Hassan, Zeinab A. (Springer, 2026)
Background Stunting is a serious health problem in Egypt. Stunting rates and height-for-age z-score (HAZ) distributions changed notably in Egypt over time, yet the factors that led to these changes remain unknown. This study examines the factors associated with these changes and provides important considerations for designing interventions to achieve the Sustainable Development Goal (SDG) of ending all forms of malnutrition by 2030.